Growth of Red Sengon (Albizia chinensis (Osbeck) Merr.) Seedlings on the Molded Seedling Media and Its Comparison with Polybag Seedling (Jurnal Penelitian Kehutanan Wallacea, 2018)
The development of alternative methods for land and forest rehabilitation is necessary for producing good quality seedlings. This study aims to examine and compare the effect of addition of mycorrhiza and rhizobium on the growth of red sengon (Albizia chinensis (Osbeck) Merr.) seedlings in molded seedling media (BMSM) and the addition of various dosages of basic fertilizers to the seedlings on polybags. Seedlings in MSM were tested in the nursery until the age of 3 months. The field test was conducted by comparing the growth of red sengon (6 months after planting) seedlings from the BMSM and seedlings on polybags. The design used was a randomzed block design. BMSM that has been added with 3 g of rhizobium per seedling gave the best growth seedling and plant growth in the field. The growth of the seedling on polybags was increased by giving basic fertilizer of 5 kg per planting hole. Red sengon seedlings originated from seedling in BMSM with the addition of 3 g of rhizobium and seedlings on polybag with a dosage of 5 kg basic fertilizer had the highest growth. BMSM as an alternative technology for tree seedling production can be used for planting, and land or forest rehabilitation.
Keywords: Albizia chinensis; Seedling; Planting programme; Rehabilitation; Rhizobium